PELATIHAN INOVASI PROYEK SAINS: KREASI HERBARIUM BAGI SISWA SMP - Dian Dwi Putri Ulan Sari Patongai; Faisal Faisal; Arifah Novia Arifin; Oriny Tri Ananda; Andi Rahmat Saleh; Andi Citra Pratiwi; Aswida Aswida (Jurnal Abdi Negeriku, 2025)
Gowa Regency has abundant natural and cultural resources that hold potential for educational development. However, these resources have not been fully utilized in science learning at the junior high school level, including at SMP Negeri 1 Gowa, due to limited facilities and insufficient teacher training. This community service program aimed to empower students and teachers with relevant science and technology skills through project-based innovation training focused on herbarium creation. Herbarium, as a collection of preserved plants, serves as an effective learning medium to enhance biological concept understanding and foster conservation awareness. The program involved socialization, hands-on herbarium-making training, technology integration, mentoring, program sustainability, and final reflection. Data were collected through observation, tests, and reflection, and were analyzed descriptively. The results indicated that students successfully produced herbarium collections, demonstrating improvements in conceptual understanding, practical skills, and creativity. Teachers also gained experience in designing project-based learning aligned with the Merdeka Curriculum principles, enhancing their instructional competence in science education. Keywords: Training, Science Innovation, Herbarium, Merdeka Curriculum